Producing "Enemy Intelligence": Information Infrastructure and the Smart City in Northwest China. (Information & Culture, 2022)
Infrastructure power announces the priorities of a state: who and what is authorized to move and act, whose lives and what materials have significance. In the colonial context of the Uyghur region in Northwest China, surveillance systems—checkpoints, cameras, digital forensic tools, and nearly sixty thousand low-level "grid workers"—build forms of infrastructure power that make hidden or resistant populations appear legible, decoded, and editable as "enemy intelligence." Drawing on a recently obtained internal police database of thousands of Chinese-language digital files, ethnographic observations, and interviews with Muslims who recently fled from China to Kazakhstan, this article argues that in this location at the frontier of the neoliberal and illiberal East, a smart city functions in part as a neo-Taylorist assembly line that employs an army of grid workers to produce Muslim enemies and non-Muslim friends.